Meningkatkan Hasil Belajar IPA Melalui Metode Pemecahan Masalah (Problem Solving Method) - Siti Rokhani (Pedagogik: Jurnal Pendidikan, 2021)
The purpose of implementing this CAR is to improve science learning outcomes by applying problem-solving methods to students in class IX-B SMPS Muhammadiyah Buntok in science learning. This CAR is expected to provide benefits for both students and teachers. Benefits for students, which can help students to understand the subject matter more quickly. At the same time, the benefits for teachers include providing choices of effective learning strategies in improving the quality of the process and student learning outcomes in science learning. The data from the learning observations were analyzed together with collaboration partners, then interpreted based on the literature review and the experiences of the researcher teachers and partner teachers. At the same time, student learning outcomes were analyzed based on the provisions of learning completeness, namely by comparing the scores obtained by students with the Minimum Completeness Criteria (KKM). In this study, the KKM score was determined to be70. A student was declared to have achieved complete learning if he obtained a score of more than/equal to 70. The results of this study indicate a significant increase in both student activity and the value of learning outcomes. The increase in student activity is characterized by the rise in the number of active students in the learning process in each cycle. While the increase in student learning outcomes as evidenced by the increase in the number of students who can score more than or equal to the KKM, which is 78.57% in the first cycle, increasing to 96.42% in the second cycle. Besides, the average value of student learning outcomes also increased from 74.99 in the first cycle to 90.85 in the second cycle.